New additions to Gatekeeper series - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Intensification of agriculture in semi-arid areas: lessons from the Kano close-settled zone, Nigeria